Comparing risk transfers under different procurement arrangements - Witt, Emlyn; Liias, Roode (International Journal of Strategic Property Management, 2011)
Public Private Partnerships (PPPs) may be considered to represent a range of procurement routes characterized by the integration of many project elements into a single contract with an output-based pricing mechanism. At the other end of the same continuum of procurement routes are less integrated arrangements with more input-based pricing (‘traditional’ procurement). Risk transfer from the client to the contractor should vary with procurement route attribute values: with greater integration and more output-based pricing an increase in risk transfer would be expected. The more risk transferred to the contractor, the greater the incentive for the contractor to deliver the project efficiently. The paper proposes indicators of risk transfer and delivery efficiency which are then used in modeling the relationships between risk transfer, efficiency and procurement route attributes. The proposed model enables the mi croeconomic assumptions which underlie PPPs to be tested with data from historical construction projects in order to cast light on the effectiveness of the PPP approach. First Publish Online: 4 Jul 2011